2021
DOI: 10.3389/fpsyg.2021.620745
|View full text |Cite
|
Sign up to set email alerts
|

Habits and Psychological Factors Associated With Changes in Physical Activity Due to COVID-19 Confinement

Abstract: The confinement that COVID-19 has brought about has had a negative influence on people’s psychological health. However, this impact is not widespread throughout the population, and men and women may be affected differently and it is not known what protective factors may exist. In this sense, physical activity has classically been shown to be a habit associated with psychological health. The study aimed to analyze the impact of confinement on psychological health (psychological well-being, coping, emotions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
2
16
0
4
Order By: Relevance
“…41 Many kinds of researches indicated that college student's physical activities were reduced during the lockdown period. [42][43][44][45][46] In the present study, the mean and SD of sedentary time (minutes) used daily by the students were 448.7± 73.6 and 517.8 ± 83.03 before and during lockdown respectively, which was significant (p=0.0001). GPAQ score (MET-min/week) was 1116.5 ± 125.3 before lockdown and 1149.2 ± 120.08 during the lockdown, which was also significant (p=0.0001).…”
supporting
confidence: 42%
“…41 Many kinds of researches indicated that college student's physical activities were reduced during the lockdown period. [42][43][44][45][46] In the present study, the mean and SD of sedentary time (minutes) used daily by the students were 448.7± 73.6 and 517.8 ± 83.03 before and during lockdown respectively, which was significant (p=0.0001). GPAQ score (MET-min/week) was 1116.5 ± 125.3 before lockdown and 1149.2 ± 120.08 during the lockdown, which was also significant (p=0.0001).…”
supporting
confidence: 42%
“…Therefore, these tools allow athletes to stay active, which could translate into continued healthy habits such as better sleep quality or a higher level of physical activity (Trabelsi et al, 2021). Research indicates that behavioral changes have occurred in the population during the pandemic lockdown, both in physical activity habits (Leon-Zarceño et al, 2021) and altered eating behaviors (Ammar et al, 2020b), highlighting the importance of safe physical activity in times of pandemic (Chtourou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Social distancing, fear of contagion and job uncertainty became part of our lives. In such an unpredictable and stressful situation, personal resources needed to promote psychosocial adaptation and emotional balance may be lacking, and this in turn may affect routines and habits related to everyday life and work (Cellini et al, 2020;León-Zarceño et al, 2021). In particular, into the context of Covid-19 pandemic, the risk of falling ill is weighed against the risk of losing the job and, thus, possibly compromising the living standards (Godinic et al, 2020;Rutter et al, 2020).…”
Section: Discussionmentioning
confidence: 99%